The Influence of Corruption on the Developing World: The Foreign Corrupt Practices Act, International Commerce and Africa - Dunderdale, Nellie R. (Journal of Law and Commerce, 2015)
The Foreign Corrupt Practices Act (FCPA) demonstrates the United States’ commitment to fight against bribery and corruption and the FCPA has had a substantial impact on commerce between organizations in the United States and the developing word.